Development of A Green Environment-Based Civic Obligation Module to Increase Students’ Awareness of The Environment at Kepanjen National 1 Senior High School - Yudistira, Ilham; Awaliyah, Siti; Rochmadi, Nur Wahyu (FKIP - Universitas Riau, 2025)
The research purposes was conducted due to environmental issues such as extreme climate change, uncontrolled amounts of plastic waste, global warming, etc. The study focuses on developing products that have been tested for feasibility, practicality, and effectiveness in order to increase environmental awareness. The study used an analysis, design, development, implementation, and evaluation development model. The product testing location was at State Senior High School 1 Kepanjen. Data collection techniques included questionnaires and formative tests, namely pre-tests and post-tests. Data analysis techniques included descriptive statistical analysis, paired t-tests, and n-gain tests. The study results showed that: (1) the validation test results by subject matter experts, learning experts, media experts, and limited trials on potential users obtained a score of 82.2 with a pass rating; (2) the paired t-test results using the Wilcoxon test showed an increase in learning outcomes after treatment of 0.038; (3) The effectiveness of the product falls into the ineffective category with low and moderate n-gain test results; (4) The causes of the product's ineffectiveness are the number of meetings that are not proportional to the learning objectives, as well as the absence of assignments related to the environment.